Between Informality and Digital Platforms: The Position and Legal Protection of Online Motorcycle Taxi Drivers in Indonesia's Urban Economy - Muhammad Azkia Pasya; Abdul Mujib; Isna; Bakri Agus Wijaya; Salahuddin Asy-Syahid (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
The development of the digital economy in Indonesia has given rise to new forms of informal employment, one of which is online motorcycle taxi (ojol) drivers who operate through digital platforms. Although they play an important role in supporting urban mobility and economic activity, the existing legal structure does not adequately protect these workers. This study aims to analyze the legal position of ojol drivers in the urban economic structure and examine how regulations and public discourse affect their legal protections. This study uses a qualitative approach with content analysis methods on legal documents, online media reports, and interviews with members of the online motorcycle taxi (ojol) driver community in Indonesia. The results show that the partnership scheme implemented by platform companies places drivers in a legally vulnerable position because they are not recognized as workers and lose access to basic labor rights. This ambiguity in legal status is exacerbated by the absence of responsive regulations at the national and regional levels. Under these conditions, the law tends to function as an instrument for legitimizing the dominance of platform corporations rather than as a means of protection and social justice. This research contributes to strengthening the socio-legal perspective in the study of digital economy law by viewing the law as an arena of power relations and providing an argumentative basis for the formulation of progressive and inclusive regulations to ensure the recognition and protection of the basic rights of online motorcycle taxi (ojol) drivers as part of the modern employment structure. [Perkembangan ekonomi digital di Indonesia telah melahirkan bentuk-bentuk pekerjaan informal baru, salah satunya adalah pengemudi ojek online (ojol) yang beroperasi melalui platform digital. Meskipun mereka memainkan peran penting dalam mendukung mobilitas perkotaan dan aktivitas ekonomi, struktur hukum yang ada tidak cukup melindungi pekerja ini. Studi ini bertujuan untuk menganalisis posisi hukum pengemudi ojol dalam struktur ekonomi perkotaan dan meneliti bagaimana regulasi dan diskursus publik memengaruhi perlindungan hukum mereka. Studi ini menggunakan pendekatan kualitatif dengan metode analisis konten pada dokumen hukum, laporan media online, dan wawancara dengan anggota komunitas pengemudi ojek online (ojol) di Indonesia. Hasil penelitian menunjukkan bahwa skema kemitraan yang diterapkan oleh perusahaan platform menempatkan pengemudi dalam posisi hukum yang rentan karena mereka tidak diakui sebagai pekerja dan kehilangan akses terhadap hak-hak kerja dasar. Ketidakjelasan status hukum ini diperparah oleh ketidakhadiran regulasi yang responsif di tingkat nasional dan regional. Dalam kondisi ini, hukum cenderung berfungsi sebagai alat untuk melegitimasi dominasi perusahaan platform daripada sebagai sarana perlindungan dan keadilan sosial. Penelitian ini berkontribusi dalam memperkuat perspektif sosiologis-hukum dalam studi hukum ekonomi digital dengan memandang hukum sebagai arena hubungan kekuasaan dan memberikan landasan argumen untuk formulasi regulasi progresif dan inklusif guna memastikan pengakuan dan perlindungan hak-hak dasar pengemudi ojek online (ojol) sebagai bagian dari struktur ketenagakerjaan modern].